Peranan Filsafat sebagai Landasan Pengembangan Pendidikan Bahasa - Rahmaizar, Rahmaizar; Novita, Yumelta; Harlita, Harlita; Maryati, Roni; Lestari, Frida Nur; Marsis, Marsis (Universitas Islam Sumatera Utara, 2025)
Language in human life functions not only as a means of communication but also as a medium for expressing thought, culture, and identity. The philosophy of language emerges as a branch of knowledge that examines the essence of language, its relation to the world, and the processes through which it is formed. Within the development of linguistic studies, the philosophy of science plays a crucial role in providing foundational perspectives. This study aims to analyze the role of philosophy of science in advancing linguistic scholarship. The research employed a systematic literature review (SLR) by identifying and screening relevant articles aligned with the research questions and objectives. Following the screening process, two relevant articles were selected to strengthen the analysis. The findings reveal that philosophy of science contributes to the growth of linguistic knowledge by examining its epistemological foundations, particularly how linguistic knowledge is acquired and understood, and by mapping the interrelations between linguistics and other disciplines. Furthermore, it provides theoretical, methodological, and critical foundations that guide the development of linguistic theories and applications. Through a holistic and reflective approach, philosophy of science encourages scholars to critically examine underlying assumptions, broaden perspectives, and deepen understanding of the role of language in society and human life.